Recombinant Human IFNα-2b Response Promotes Vaginal Epithelial Cells Defense against Candida albicans - Li, Ting; Niu, Xiaoxi; Zhang, Xu; Wang, Suxia; Liu, Zhaohui (Frontiers in Microbiology, 2017)
Classical antifungal drugs have been subjected to restrictions due to drug toxicity, drug resistance, bioavailability, and detrimental drug interactions. Type I interferon (IFN) exerts direct distinct immunostimulatory or immunomodulatory actions; however, little is known regarding the anti-fungal reactions of vaginal epithelial cells induced by the type I IFN response. Therefore, in the present study, we evaluated the cytotoxic activity, immunocompetent cytokine responses, and non-B IgG production of the VK2/E6E7 vaginal epithelial cell (VEC) line following recombinant human IFN α-2b (rhIFNα-2b) treatment in response to Candida albicans. When treated with rhIFNα-2b, the production of IL-2, IL-4, and IL-17 were significantly up-regulated compared to the infected control cells (P < 0.05). Our scanning electron microscopy results revealed that C. albicans can invade VECs by inducing both endocytosis and active penetration. RhIFNα-2b was able to transform the VECs into a thallus and stretched pattern, promoting the fusion of filopodia to form a lamellipodium and enhancing the mobility and the repair capacity of the VECs. In addition, rhIFNα-2b could effectively inhibit the adhesion, hyphal formation, and proliferation of C. albicans. Collectively, these responses restored the immune function of the infected VECs against C. albicans in vitro, providing a theoretical basis for this novel treatment strategy.